2017
DOI: 10.11138/mltj/2017.7.2.263
|View full text |Cite
|
Sign up to set email alerts
|

Reverse shoulder arthroplasty patient personalized rehabilitation protocol. Preliminary results according to prognostic groups

Abstract: SummaryBackground: Rehabilitation after Reverse Shoulder Arthroplasty (RSA) is still object of discussion with no based evidence guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…Reducing readmission rates may call for changes in healthcare practices and increased communication with patients on the importance of self-motivated preoperative health optimization. In fact, validated postoperative reverse TSA rehabilitation protocols are lacking, and Oliva et al showed that personalized postoperative treatment protocols specific to patients stratified by perioperative risks can decrease complication rates [18]. High-risk patients treated with frequent physician consultations with established goals of recovery and adjusted rehabilitation protocols are shown to have improved clinical results and decreased complications [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reducing readmission rates may call for changes in healthcare practices and increased communication with patients on the importance of self-motivated preoperative health optimization. In fact, validated postoperative reverse TSA rehabilitation protocols are lacking, and Oliva et al showed that personalized postoperative treatment protocols specific to patients stratified by perioperative risks can decrease complication rates [18]. High-risk patients treated with frequent physician consultations with established goals of recovery and adjusted rehabilitation protocols are shown to have improved clinical results and decreased complications [18].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, validated postoperative reverse TSA rehabilitation protocols are lacking, and Oliva et al showed that personalized postoperative treatment protocols specific to patients stratified by perioperative risks can decrease complication rates [18]. High-risk patients treated with frequent physician consultations with established goals of recovery and adjusted rehabilitation protocols are shown to have improved clinical results and decreased complications [18]. As the landscape of healthcare economics shifts to value patient satisfaction outcomes, diabetes status is important to consider as part of a stratified rehabilitation protocol for a growing elderly population with inherent risk factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is related with an enhancive number of complications and postoperative discomforts [15,20,22,5660]. In particular, the occurrence of SS fractures has a prevalence ranging from 0.8% to 10.2% [6,13,14,16,20,22,56,58,6068]. As far as we know, few studies have put forward the variable anatomy of SS [5154].…”
Section: Discussionmentioning
confidence: 99%
“…Bioactive glass was added both between the stem and cones, and as a proximal humerus augmentation ( Figure 5 and Figure 6 ) in order to improve defect filling and attempt to avoid a new infection, thus increasing implant stability and integration. The surgical technique has already been described in detail [ 48 ]. The high porosity of these cones results in satisfactory primary fixation on recipient bone and cement fixation on the intramedullary side, sealing the component.…”
Section: Bone Loss Management—tantalum Conesmentioning
confidence: 99%